Lathrolestes (Hymenoptera, Ichneumonidae) from Central Asia, with a key to the species of the tripunctor species-group - Reshchikov, Alexey (Zootaxa, 2012)
Six new species of Lathrolestes (Hymenoptera, Ichneumonidae) are described from Central Asia: L. obliquus sp. nov.from Tadjikistan, Turkmenistan, Uzbekistan, Kyrgyzstan; L. aitmatovi sp. nov. from Kyrgyzstan; L. kozlovi sp. nov. fromInner Mongolia, China; L. hovdensis sp. nov. from Mongolia; L. grahami sp. nov. from Sichuan, China; and L. ruficaudussp. nov. from Tadjikistan. The tripunctor species-group is established and an illustrated key to species of this speciesgroup is provided.